Snowball to avalanche - Chiu, Hung-Chang; Pant, Anurag; Hsieh, Yi-Ching; Lee, Monle; Hsioa, Yi-Ting; Roan, Jinshyang (European journal of marketing, 2014)
Purpose – This paper aims to investigate the determinants of successful online viral marketing. More companies in recent years have reduced their advertising expenditures on traditional media. Instead, they focus more on word-of-mouth marketing to reach their potential customers. Design/methodology/approach – A 2 (high/low utilitarian message context) × 2 (high/low hedonic message context) × 2 (message source: strong/weak tie strength) × 2 (channel: e-mail/blog) between-subjects experiment was conducted. A total of 363 completed questionnaires were collected in Taiwan. Findings – The findings are fourfold. First, the greater the tie strength between the sender and the receiver, the more actively they share information. Second, an audience is more willing to share a message with others when the message contains higher degrees of utilitarian or hedonic values. Third, those who are highly involved with the products are more willing to share information than those who are less involved. Fourth, those who access the information via blogs are more willing to share information with others. Research limitations/implications – The first limitation pertains to the issue of external validity. Also, to maximize internal validity, hypothetical scenarios and experimental designs were used rather than actual e-mail/blog experiences as stimuli. The results of this study provide some key strategic implications for companies that are seeking to enhance a successful viral marketing campaign. Practical implications – This study suggests there is no “one size fits all” answer. A successful viral marketing campaign is specific to individual characteristics and the approaches used. Originality/value – The present study combines related research – including communication theory, consumer value and involvement theory – to investigate the determinants of individuals’ intentions to share marketing information.